The Influence of Workplace Spirituality and Organizational Culture on Employee Performance with the Mediating Variable Individual Spirituality at PT. Tirtakencana Tatawarna Garut Regency, West Java - Atep Muhammad Lutfi (GoAcademica Research & Publishing, 2023)
Development and improvement of human resources in facing the challenges of the world of work related to the application of spiritual values ​​in the workplace, the values ​​of the company's organizational culture, both individual and group levels, are considered to have an important role in improving employee performance. This research aims to determine the effect of workplace spirituality and organizational culture on Employee performance with individual spirituality as a mediating variable at PT. Tirtakencana Tatawarna, Garut Regency, West Java. This research uses quantitative methods with types of purposive sampling, data processing, and testing using SEMPLS version 3.9.2. The research results show that there is a significant and positive direct influence, this means that the higher workplace spirituality, organizational culture, and individual spirituality, the higher employee performance, conversely, if workplace spirituality, organizational culture, and individual spirituality are low, employee performance will be low. Indirectly, it has been proven that individual spirituality mediates significantly and positively.